Phase 1 clinical trial on Orgasmic Meditation (OM): Assessing safety and feasibility as a meditation practice for individuals with PTSD - Daniel Kriegman; Rachel Pelletier; Caroline Griggs; Caryn Roth (Contemporary Clinical Trials Communications)
Background: We measured the safety and efficacy of a treatment protocol that includes Orgasmic Meditation (OM), a structured attention training practice conducted between two people who follow a predefined set of detailed instructions. The practice involves one person gently stroking the clitoris of the other person for 15 minutes while both place their attention on the point of contact and notice what they feel. Practitioners of OM have reported that this practice is distinct both from typical sexual engagement and other forms of meditation (Siegel et al., 2022). Methods: Approved by Advarra Pro00061665. The study involved 28 participants (14 pairs), who were recruited based on residence in the Massachusetts area, being in a relationship, and having no history of practicing OM. Twenty-three of these participants identified and scored as having PTSD symptoms (PCL-5 scores >31). Participants were instructed to perform the OM practice a minimum of 12 times over a 4-week period and met weekly with the principal investigator to determine if any safety issues were manifesting. A series of surveys (Daily: Tumescence Survey and OM journal. Baseline and weekly: PCL-5. Baseline, completion and follow up: Eudaimonia assessment, PHQ-9, Gad-7, BIPF, and OM perception survey at) were administered to measure the results. Results: Orgasmic Meditation showed positive results in persons with PTSD. Orgasmic meditation is safe and may offer improvement in symptoms. OM showed 47 % improvement in PTSD scores Average score decreased from 60 to 28. Average score across 23 participants rate 4.9/5 that OM is safe. Conclusion: These results suggest that Orgasmic Meditation may be safe for this traumatized population, and may ameliorate symptoms of PTSD. Further research appears to be warranted to determine the efficacy of OM in treatment of PTSD.